Investigating the Challenges of Developing Sports among the Elder Lies in Hamedan Province and Presenting Practical Solutions - Rasul Monem (Journal of Global Pharma Technology, 2017)
The aim of this study was to determine the challenges of developing sports among the elderlies in Hamadan Province and their problems with exercising as well as providing practical solutions for developing recreational sports for this group of people in Hamadan Province. In order to investigate the research question, elder lies above 60 in 2014 were chosen as the statistical population. The sampling method was cluster-random and the data collection instrument was a researcher-made questionnaire which its face and content validity were tested and confirmed by a group of authorities. The reliability was calculated using cronbach-α (α=0.87).Data analysis indicated that there are significant relationships. between monthly income and engaging in sports activities, between elder lies` satisfaction from leisure time activities and the kind of activity, and  between quality of life and doing sports among the elderlies at α= 0.05. Findings of the present study indicated that lack of sufficient recreational and sports facilities, low level of education, low income, physical weakness, cultural factors, mental features, family , and proper education about advantages of sports and physical activity, and spending leisure time have prominent roles in proper use of sports and leisure time. Authorities in Hamadan province should take some serious steps including creating sports-recreational spaces and places in order to remove obstacles the elder lies face to increase elder lies` tendencies to sports.Keywords: Leisure Time, Sports Activity, The elderly.